First, solve the first equation for y:
y = 2 + 3x
Next, substitute this expression for y into the second equation:
4x - 3(2 + 3x) = -16
4x - 6 - 9x = -16
-5x - 6 = -16
-5x = -10
x = 2
Now that we have x = 2, substitute it back into the first equation to find y:
y = 2 + 3(2)
y = 2 + 6
y = 8
Therefore, the solution to the system of equations is (2, 8).
Solve the system of two equations using substitution.
y=2+3x
4x−3y=−16 (1 point)
Responses
(2, 10)
left parenthesis 2 comma 10 right parenthesis
(−2, 4)
left parenthesis negative 2 comma 4 right parenthesis
(−2, −4)
left parenthesis negative 2 comma negative 4 right parenthesis
(2, 8)
left parenthesis 2 comma 8 right parenthesis
1 answer